S57 Predictors of uptake of ambulatory oxygen on completion of the ambox trial, a study to assess effects of ambulatory oxygen on quality of life in patients with fibrotic interstitial lung disease. (15th November 2017) - Mori, L; Canu, S; Visca, D; Tsipouri, V; Bonini, M; Pavitt, M; Fleming, S; Firouzi, A; Farquhar, M; Leung, E; Hogben, C; Lauretis, A De; et al.
Abstract : Background: There are no ILD specific guidelines on the use of ambulatory oxygen. The AmbOx trial is a multicenter, randomised, cross-over controlled trial (NCT02286063 ), to assess quality of life during two weeks on ambulatory oxygen compared to two weeks off oxygen, in patients with fibrotic ILD. Methods: Individuals with fibrotic ILD whose oxygen saturation was normal at rest, but dropped to ≤88% on a 6MWT, with stable symptoms during a two week run-in period, were recruited and randomised. Primary outcome: health status assessed by King's Brief ILD questionnaire (KBILD). A simple question on whether breathlessness had changed (better, same, worse) over the previous two weeks was a key secondary outcome. Patients' experiences with portable oxygen were explored through interviews in a subgroup. At the end of the four week trial period, patients were asked if they wished to continue with the ambulatory oxygen. Results: Out of 84 randomised patients, 76 completed the trial. Mean age 64.5±1.1 years, 58 males, 53 ever smokers, FVC 73.3%±19.1%, DLCO 38.7%±12.8%. 43 patients had possible/definite IPF. Ambulatory oxygen, compared to no oxygen, was associated with improvements in total KBILD score (p<0.0001). At the end of the two weeks on oxygen, the majority of patients reported improved breathlessness (better:52/76 – same:23/76 – worse:1/76), compared to the two weeks on no oxygen (better 1/76 – same:57/76 – worse:18/76). On trial completion, 51/76 (67%) of patients chose to continue on ambulatory oxygen. On multivariate analysis, factors independently predictive of the patient's decision to continue, included younger age (64.8 vs 72.8 years, p=0.002), more severe disease (CPI 55.5 vs 49.1, p=0.003) and patient's global assessment of improvement in breathlessness (OR 3.2, p=0.018). Despite symptomatic improvements in the majority, ambulatory oxygen was also associated with a number of patient-reported challenges, explored in the patient interviews.